The Role of Traditional Games in Developing Children’s Social and Creative Competence in Community-Based Education - Mardiani, Desika Putri; Lestari, Gunarti Dwi; Hariyati, Nunuk; Widodo; Lestari, Tri (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Digitalization has expanded children’s access to learning resources but reduced opportunities for direct social interaction and culturally grounded play. In community education contexts, traditional games offer a valuable yet underused pathway for supporting children’s social and creative development. However, limited empirical evidence explains their role as policy-relevant tools in structured community-based education systems. This study examines the contribution of traditional games to children’s social competence and creative engagement in Indonesian community learning settings. Using a research and development design with empirical validation, the study involved 150 children across three learning sites. Data were collected through pre- and post-intervention assessments, observation, facilitator reflection, and participant feedback, and analyzed using descriptive statistics, paired-sample t-tests, correlation analysis, effect sizes, and thematic analysis. Findings show that structured traditional game activities improved communication, cooperation, problem-solving, initiative, and adaptive participation. Qualitative results indicate enhanced collaboration, role negotiation, cultural engagement, and creative exploration. The study positions traditional games as sociocultural learning mechanisms and provides policy-relevant evidence for integrating them into community education programs.